Greater Use Of Preventive Services In U.S. Health Care Could Save Lives At Little Or No Cost - Maciosek, Michael V.; Coffield, Ashley B.; Flottemesch, Thomas J.; Edwards, Nichol M.; Solberg, Leif I. (Health Affairs, 2010)
There is broad debate over whether preventive health services save money or represent a good investment. This paper analyzes the estimated cost of adopting a package of twenty proven preventive services--including tobacco cessation screening, alcohol abuse screening, and daily aspirin use--against the estimated savings that could be generated. We find that greater use of proven clinical preventive services in the United States could avert the loss of more than two million life-years annually. What's more, increasing the use of these services from current levels to 90 percent in 2006 would result in total savings of $3.7 billion, or 0.2 percent of U.S. personal health care spending. These findings suggest that policy makers should pursue options that move the nation toward greater use of proven preventive services.